1988
DOI: 10.1159/000180961
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Thyroxine Administration for Idiopathic Respiratory Distress Syndrome in Preterm Infants

Abstract: Thirty-six preterm infants of less than 34 weeks of gestation with idiopathic respiratory distress syndrome (IRDS) were studied. Eighteen of them were treated with intravenous thyroxine (T4) and compared with 18 control prematures to evaluate the effect of postnatal T4 administration on the course of IRDS. After treatment, serum T4 levels were similar to those of healthy term infants. No statistically significant effect on mortality rate, duration of mechanical ventilation (p >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 12 publications
0
14
0
5
Order By: Relevance
“…In developing CLD, pneumocyte proliferation and surfactant synthesis may require larger amounts of thyroid hormones than in healthy individuals. In IRDS of preterm infants, hypothyroxinemia does not seem to be an etiological factor [14,23]. Recently Job et al [14] have demonstrated unaltered free T 4 levels in IRDS between day 2 and day 7.…”
Section: Discussionmentioning
confidence: 98%
“…In developing CLD, pneumocyte proliferation and surfactant synthesis may require larger amounts of thyroid hormones than in healthy individuals. In IRDS of preterm infants, hypothyroxinemia does not seem to be an etiological factor [14,23]. Recently Job et al [14] have demonstrated unaltered free T 4 levels in IRDS between day 2 and day 7.…”
Section: Discussionmentioning
confidence: 98%
“…Il secondo motivo è giustificato dal fatto che alcuni AA. propongono di effettuare la profilassi per l'Ipotiroidismo Transitorio del neonato ELGAN a partire dal 2°-3° giorno di vita [12][13][14][15][16][17][18][19][20].…”
Section: Discussioneunclassified
“…Tuttavia è determinante per il clinico avere un punto di riferimento preciso da cui partire, per stabilire se i livelli di TSH e T4 di un determinato bambino incrementano o diminuiscono nei giorni successivi alla nascita. I lavori svolti, concernenti la somministrazione di ormoni tiroidei alla nascita nel neonato pretermine, hanno dimostrato risultati discordanti, per quanto riguarda sia il deficit neurocognitivo di tali soggetti, sia l'incidenza di distress respiratorio e di BPD [11][12][13][14][15][16][17][18][19][20]. Attualmente infatti non esistono indicazioni precise, in rapporto agli studi effettuati, per somministrare gli ormoni tiroidei a tutti i soggetti ELGAN.…”
Section: Discussioneunclassified
See 1 more Smart Citation
“…However mental outcome in a subgroup of T 4 -treated infants less than 27 wk gestation was significantly better than in the placebo infants when tested at 2 y of age. Two studies examining respiratory factors as end points, one giving T 4 (12) and another T 3 (13), have not shown any clear-cut benefit.…”
mentioning
confidence: 99%